Wordpress : the missing manual : the book that should have been in the box - MacDonald, Matthew (Missing manual., 2020)
Whether you're a budding blogger or seasoned web designer, WordPress is a brilliant tool for creating websites--once you know how to tap into its impressive features. The latest edition of this jargon-free Missing Manual shows you how to use WordPress's themes, widgets, and plug-ins to build just about any kind of site.